Karakterisasi Morfologi Tetua dan Hybrid Anggrek Dendrobium bigibbum dan Dendrobium lineale - Hartati, Sri; Nandariyah, Nandariyah; Muliawati, Endang Setia; Sukaya, Sukaya; Yuniastuti, Endang; Parjanto, Parjanto; Manurung, Ida Rumia (Universitas Sebelas Maret, 2022)
Dendrobium are one of the most cultivated ornamental orchids plants. However, orchids as genetic resources have not been optimally utilized as parents in crossing to produce offspring according to the characteristics desired by consumers. This study aims to study the similarities between the Hybrid results of crosses compared to their parent orchids and obtain a new variety of Hybrid from crosses of Dendrobium bigibbum and Dendrobium lineale. This research was conducted at the Bogor Botanical Gardens and Plosorejo Village, Matesih District, Karanganyar Regency, Central Java. The materials used were 14 samples of orchid plants, including three examples of D. bigibbum orchids, three samples of D. lineale orchids, four samples of Hybrid plants resulting from crosses of ♀ D. bigibbum X ♂ D. lineale, and four samples of Hybrid plants from crossing ♀ D. lineale X ♂ D. bigibbum. Observation variables include quantitative variables. The quantitative morphological variables use the guideline developed by BALITHI. To analyze the data using the program of NTSYSpc 2.02i version. The results showed that based on quantitative observations, Dendrobium lineale as a female parent can change the size of the dorsal sepal width, flower arrangement length, lateral sepal length, and flower length. And Dendrobium bigibbum as the female parent can change the size of the petal length, lateral sepal width, flower width, pseudobulb thickness, pseudobulb length, leaf length, and leaf width.